tDCS Task-Oriented Approach Improves Function in Individuals With Fibromyalgia Pain. A Pilot Study - Morin, Marika; St-Gelais, Raphaël; Ketounou, Kossi Épiphane; d'Assomption, Régis M.-L.; Ezzaidi, Hassan; Fernandes, Karen B. P.; da Silva, Rubens A.; Ngomo, Suzy (Frontiers in Pain Research, 2021)
Fibromyalgia (FM) is a complex pain syndrome accompanied by physical disability and loss of daily life activities. Evidences suggest that modulation of the primary motor cortex (M1) by transcranial direct current stimulation (tDCS) improves functional physical capacity in chronic pain conditions. However, the gain on physical function in people living with FM receiving tDCS is still unclear. This study aimed to evaluate whether the tDCS task-oriented approach improves function and reduces pain in a single cohort of 10 FM. A total of 10 women with FM (60.4 ± 15.37 years old) were enrolled in an intervention including anodal tDCS delivered on M1 (2 mA from a constant stimulator for 20 min); simultaneously they performed a functional task. The anode was placed on the contralateral hemisphere of the dominant hand. Outcome assessments were done before the stimulation, immediately after stimulation and 30 min after the end of tDCS. The same protocol was applied in subsequent sessions. A total of five consecutive days of tDCS were completed. The main outcomes were the number of repetitions achieved and time in active practice to evaluate functional physical task performance such as intensity of the pain (visual analog scale) and level of fatigue (Borg scale). After 5 days of tDCS, the number of repetitions achieved significantly increased by 49% (p = 0.012). No change was observed in active practice time. No increase in pain was observed despite the mobility of the painful parts of the body. These results are encouraging since an increase in pain due to the mobilization of painful body parts could have been observed at the end of the 5th day of the experiment. These results support the use of tDCS in task-based rehabilitation.